Interprofessional collaboration in aesthetic correction rehabilitation: Kerjasama antar profesi dalam merehabilitasi koreksi estetik - Maulida, Nurul Safira; Risnawati; Hutami, Astri Al; Utama, Mohammad Dharma; Machmud , Edy (Makassar Dental Journal PDGI Makassar, 2025)
Interprofessional teamwork is essential in performing medical procedures to ensure effective and efficient healthcare services. This case report discusses teamwork at the Hasanuddin University Dental and Oral Health Education Hospital in rehabilitating a case that required interprofessional collaboration. A 17-year-old female patient came to the Prosthodontics Clinic of the Hasa-nuddin University Dental and Oral Hospital, referred from the Pedodontics Department, which had performed root canal treatment due to a fractured upper front tooth caused by a traffic accident. A post crown was made on the fractured tooth 12 and a veneer was applied to the upper anterior jaw to correct the rotation and improve aesthetics. It was concluded that the treatment using an interprofessional collaborative approach in rehabilitating cases requiring aesthetic correction was successfully performed, and the patient was satisfied.